Optoelectronic oscillation of the second harmonic of a period-one oscillating distributed feedback laser - Chen, Guangcan; Lu, Dan; Guo, Lu; Zhao, Wu; Huang, Yongguang; Zhao, Lingjuan (Optik (Stuttgart), 2019)
The optoelectronic oscillation using the second harmonic of a period-one (P1) oscillation as the oscillation seed is proposed and experimentally demonstrated. The P1 oscillation was generated by a distributed feedback (DFB) laser subject to optical feedback. By using a bandpass electrical amplifier to provide sufficient gain for the second harmonic frequency of the P1 oscillation, frequency-doubled microwave signal was generated with the single sideband phase noise below -114.2 dBc/Hz at a 10-kHz frequency offset from the carrier.